Lissothuria caboblanquensis n. sp., a new species of sea cucumber (Holothuroidea: Dendrochirotida: Psolidae) from Costa Rica - Arriaga Ochoa, Julio A. (2014)
A new species of sea cucumber of the genus Lissothuria Verrill, 1867 is described. Lissothuria caboblanquensis n. sp. was found in the Costa Rican Pacific, at 17 m depth. The presence of towers with spiny apex and the elaborated shape of the hourglasses in the dorsal body wall, make this species unique among the species of this genus. This species is distinctive within the genus. The shape of the ossicles shows some similarities with L. nutriens H. L. Clark, 1901 and L. hancocki (Deichmann, 1941).